Site-Specific Basal Body Duplication in Chlamydomonas - O’Toole, Eileen T. (2013)
Correct centriole/basal body positioning is required for numerous biological processes, yet how the cell establishes this positioning is poorly understood. Analysis of centriolar/basal body duplication provides a key to understanding basal body positioning and function. Chlamydomonas basal bodies contain structural features that enable specific triplet microtubules to be specified. Electron tomography of cultures enriched in mitotic cells allowed us to follow basal body duplication and identify a specific triplet at which duplication occurs. Probasal bodies elongate in prophase, assemble transitional fibers (TF) and are segregated with a mature basal body near the poles of the mitotic spindle. A ring of nine-singlet microtubules is initiated at metaphase, orthogonal to triplet eight. At telophase/cytokinesis, triplet microtubule blades assemble first at the distal end, rather than at the proximal cartwheel. The cartwheel undergoes significant changes in length during duplication, which provides further support for its scaffolding role. The uni1-1 mutant contains short basal bodies with reduced or absent TF and defective transition zones, suggesting that the UNI1 gene product is important for coordinated probasal body elongation and maturation. We suggest that this site-specific basal body duplication ensures the correct positioning of the basal body to generate landmarks for intracellular patterning in the next generation.